Developing a conceptual framework for Zakat collection and distribution Impact on social welfare through implications of SDGs - Ashurov, Sharofiddin; Syed Jaafar Alhabshi, Syed Musa; Othman, Anwar Hasan Abdullah; Mohammad, Habibullah; Muhamad Yusof, Mohd Sukri (IGI Global Publisher, 2021)
Although Islamic social finance including zakat has witnessed an upsurge in development in quantum, which reached US$2 trillion in 2015 and is projected to exceed US$3 trillion by 2020, due to a lack of transparency, trust, and timely disclosure to public has resulted in inefficient of zakat collection and ineffective disbursement for the wellbeing of recipients. The reason for this could be neglecting adoption of financial technology specifically blockchain and artificial intelligence system in zakat management to enhance proper collection and efficient distributions timely and effectively reporting to public. Therefore, this research proposes an ‘Islamic Social Welfare Financial Technology' (ISW FinTech) as an innovative framework that assesses zakat institutions operational efficiency of zakat collection, transparency, and effective distribution that would lead to well being of zakat recipients. This framework is based on new six clusters according to their needs and priority, which convert them from being zakat recipients into zakat payers.